Pengaruh Konseling Keperawatan terhadap Tingkat Kecemasan Pasien dengan Penyakit Kronis di Wilayah Kerja UPT Puskesmas Gunungsari - Sri Maryani (Journal of Nursing Perspectives, 2025)
Patients with chronic diseases frequently experience anxiety related to prolonged treatment, physical limitations, fear of complications, and uncertainty about disease prognosis, which may negatively affect treatment adherence and overall well-being. In primary healthcare settings, nurses have a pivotal role in addressing psychosocial problems through holistic nursing care, including structured nursing counseling. This study aimed to examine the effect of nursing counseling on anxiety levels among patients with chronic diseases in the working area of UPT Puskesmas Gunungsari. A quasi-experimental study with a pretest–posttest design was conducted involving patients diagnosed with chronic conditions who met the inclusion criteria and were selected using purposive sampling. Anxiety levels were assessed before and after the intervention using a standardized and validated anxiety measurement tool. The nursing counseling intervention was delivered through structured individual sessions focusing on emotional support, health education, coping strategies, and problem-solving related to disease management, conducted by trained nurses in the primary care setting. Statistical analysis was performed to compare anxiety scores before and after the intervention using appropriate inferential tests. The results demonstrated a significant reduction in anxiety levels among patients following the nursing counseling intervention, indicating that counseling effectively alleviated anxiety in patients with chronic diseases. These findings support previous evidence that psychosocial nursing interventions can improve mental health outcomes and enhance patient adaptation to chronic illness (Stuart, 2013; Townsend & Morgan, 2021). In conclusion, nursing counseling is an effective and feasible intervention to reduce anxiety among patients with chronic diseases in primary healthcare services. Integrating structured nursing counseling into routine nursing care at community health centers is recommended to promote mental well-being, strengthen patient-centered care, and support comprehensive chronic disease management.